2019
DOI: 10.1111/desc.12886
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving gaze from head and eye rotations: An integrative challenge for children and adults

Abstract: Gaze is an emergent visual feature. A person's gaze direction is perceived not just based on the rotation of their eyes, but also their head. At least among adults, this integrative process appears to be flexible such that one feature can be weighted more heavily than the other depending on the circumstances. Yet it is unclear how this weighting might vary across individuals or across development. When children engage emergent gaze, do they prioritize cues from the head and eyes similarly to adults? Is the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 49 publications
(66 reference statements)
1
20
0
Order By: Relevance
“…Socially assistive robots are becoming increasingly popular as interventions for youth with autism. Previous studies have focused on eye contact and joint attention Mihalache et al (2020) ; Mavadati et al (2014) ; Feng et al (2013) , showing that the pattern of gaze perception in the ASD group is similar to Typically Developing (TD) children as well as the fact eye contact skills can be significantly improved after interventional sessions. These findings also provide strong evidence that ASD children are more inclined to engage with humanoid robots in various types of social activities, especially if the robots are socially intelligent Anzalone et al (2015) .…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Socially assistive robots are becoming increasingly popular as interventions for youth with autism. Previous studies have focused on eye contact and joint attention Mihalache et al (2020) ; Mavadati et al (2014) ; Feng et al (2013) , showing that the pattern of gaze perception in the ASD group is similar to Typically Developing (TD) children as well as the fact eye contact skills can be significantly improved after interventional sessions. These findings also provide strong evidence that ASD children are more inclined to engage with humanoid robots in various types of social activities, especially if the robots are socially intelligent Anzalone et al (2015) .…”
Section: Related Workmentioning
confidence: 99%
“…Participants were selected from this pool and the community with help from the University of Denver Psychology department. Six out of nine ASD participants had previous human-robot-interaction with another social robot named ZENO Mihalache et al (2020) , and three out of the nine kids from the ASD group had previous music experience on instruments other than the Xylophone (saxophone and violin). All children in the ASD group had a previous diagnosis of ASD in accordance with diagnostic criteria outlined in Association (2000) , including an ADOS report on record.…”
Section: Experiments Designmentioning
confidence: 99%
“…We found no relationship between autistic traits and cue integration during interaction perception, nor an interaction between autistic traits and FoR in Experiment 1 (Figure 5A). Previous research has shown that autism is associated with differences in cue integration during gaze perception (Ashwin et al, 2015;Mihalache et al, 2020); autisic participants utilise information from the eyes less than non-autistic participants (Mihalache et al, 2020) and focus more on body information (Ashwin et al, 2015) when judging gaze direction. Indeed, diminished attention to others' eyes is an early symptom of ASC (Jones & Klin, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Further, individuals with Autism Spectrum Conditions (ASC ) show differences in social cue 1 integration when viewing images of isolated individuals (Ashwin et al, 2015;Mihalache et al, 2020); autistic observers focus more on body than head information (Ashwin et al, 2015), and utilise information from the eyes less than non-autistic individuals (Mihalache et al, 2020), when judging the direction of an individual's gaze. These findings are potentially explained by their enhanced perception of features at the expense of global processing (Happé, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…They were approximately 7 years old (see Table 1). We selected children at this age since it is a potentially sensitive developmental period for gaze perception among children whose more basic visual mechanisms are presumably in place (Mihalache et al, 2020). And children with ASD at this age also showed the impairments of RJA (Thorup et al, 2017).…”
Section: Methods Participantsmentioning
confidence: 99%